Karakteristik Dan Manhaj Tafsir Marah Labid Karya Syekh Nawawi Al-Bantani - Masnida Masnida (IAI Darussalam, 2016)
The Qur'an is the word of Allah which contains many elements, starting with the things related to ubudiyyah mahdlah or ghairu mahdlah. To explore what is meant and desired by the Qur'an, it is a necessary tool to dissect it, that is the science of exegesis. With the science of interpretation, we are expected as a reviewer and observer of the Qur'an can understand the sciences contained in it, both the nature of khass or mujmal. The understanding and interpretation activities of the Qur'an will never be completed. Dialectics that occur also have ups and downs in conjunction with the openness, skill, and ability of an interpreter. In Indonesia, the study of Tafseer is also interesting for us to study and follow. Lots of interpreters are popping up, just a matter of Prof. Dr. Quraish Shihab with his book Tafsir al-Misbah, Prof. Dr. Hasbi Ashiddiqi with his work Tafsir an-Nur, and Sheikh Nawawi al-Bantani with his work Tafsir Marah Labid. Tafsir Angah Labid results from the thought of Sheikh Nawawi has its own uniqueness to be studied as an ingredient in the academic insight